Is the cure worse than the disease? Comparing the ecological effects of an invasive aquatic plant and the herbicide treatments used to control it - Alison Mikulyuk; Ellen Kujawa; Michelle E. Nault; Scott Van Egeren; Kelly I. Wagner; Martha Barton; Jennifer Hauxwell; M. Jake Vander Zanden (Canadian Science Publishing, 2021)
Invasive species are known to have negative ecological effects. However, few studies have evaluated the impacts of invasive species relative to the effects of invasive species control, thereby limiting our ability to make informed decisions considering the benefits and drawbacks of a given management approach. To address this gap, we compared the ecological effects of the invasive aquatic plant Eurasian watermilfoil (Myriophyllum spicatum L.) with the effects of lake-wide herbicide treatments used for M. spicatum control using aquatic plant data collected from 173 lakes in Wisconsin, USA. First, a pre-post analysis of aquatic plant communities found significant declines in native plant species in response to lake-wide herbicide treatment. Second, multi-level modeling using a large data set revealed a negative association between lake-wide herbicide treatments and native aquatic plants, but no significant negative effect of invasive M. spicatum. Taken together, our results indicate that lake-wide herbicide treatments aimed at controlling M. spicatum had larger effects on native aquatic plants than did the target of control-invasive M. spicatum. Our comparison reveals an important management tradeoff and encourages careful consideration of how we balance the real and perceived impacts of invasive species and the methods used for their control.